Penyusunan Modul Training 7 Quality Tools dan 5R Dokumen untuk Mendukung Program Continuous Improvement di PT. X - Christian Oscar Karuniawan (Jurnal Titra, 2022)
PT. X is a cigarette company that has implemented Continuous Improvement. Continuous Improvement Program at PT. X has not been able to run optimally because there is no complete explanation of the Seven Quality Tools so that employees do not understand the Seven Quality Tools, and there are no special rules regarding document storage in the 5S program so that employees are still hoarding documents that are actually rarely or no longer used. PT. X plans to train employees on the concept of Seven Quality Tools in full, as well as introduce and implement 5S in document management to employees. This study aims to create a training module on Seven Quality Tools and 5S in Document Management. The resulting Seven Quality Tools training module has been implemented in the form of trial training. Meanwhile, the 5S training module in Document Management is implemented by directly applying the module to General HR secretary and Recruitment department.